PRINCIPLES OF THERAPY OF ACUTE BRONCHIOLITHIS IN CHILDREN - Азимова Камола Талатовна; Каримова Шахнозабону (TADQIQOTLAR, 2025)
Abstract. Acute bronchiolitis is one of the most common lower respiratory tract infections in children and causes airway obstruction in 10%-30% of cases. In this regard, the aim of the study was to optimize the principles of therapy and enhance the prevention of recurrence of the disease. 54 children with acute bronchiolitis under the age of two were examined. The study revealed irrational use of antibiotics and incorrectly selected starting doses for children with acute bronchiolitis. Despite the existence of a large number of risk factors, in order to reduce the incidence of acute respiratory infections and bronchiolitis, breastfeeding should be recommended for at least the first 6 months of life. In case of bronchiolitis, antibiotic therapy is possible only in the presence of bacterial complications.